Time-moisture superposition principle in creep behavior of white oak with various earlywood vessel locations - Zhang, Yuge; Hou, Junfeng; Chen, Haili; Cen, Junjie; Jiang, Zhihong; Yu, Youming (Maderas. Ciencia y Tecnología, 2023)
Creep behavior of wood plays a fundamental role in precision processing of wood. In this work, experi- mental creep tests have been conducted to determine the influence of earlywood vessel location and moisture content on creep behavior of Quercus alba (white oak). Time-moisture superposition principle was applied to predict long-term creep behavior of white oak. Results revealed that both of instantaneous and 45-min strain of specimens increased with the increasing of moisture content and decreased with increasing distance between earlywood vessel belt and load-bearing surface significantly. Additionally, the time-moisture superposition principle was found to have feasibility to predict creep behavior of white oak with various earlywood vessel locations and moisture content ranges (6 % - 18 %). We believe that the proposed investigation was beneficial for the processing precision and civil engineering applications of wood.